2005
DOI: 10.1901/jeab.2005.69-02
|View full text |Cite
|
Sign up to set email alerts
|

Within-Subject Testing of the Signaled-Reinforcement Effect on Operant Responding as Measured by Response Rate and Resistance to Change

Abstract: Response rates under random-interval schedules are lower when a brief (500 ms) signal accompanies reinforcement than when there is no signal. The present study examined this signaled-reinforcement effect and its relation to resistance to change. In Experiment 1, rats responded on a multiple random-interval 60-s random-interval 60-s schedule, with signaled reinforcement in only one component. Response resistance to alternative reinforcement, prefeeding, and extinction was compared between these components. Lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 22 publications
3
34
5
Order By: Relevance
“…Previously it has been demonstrated that the strength of history effects such as resistance to change (e.g., Lattal, 1989;Okouchi & Lattal, 2006;Reed & Doughty, 2005) and reinstatement (e.g., Doughty et al, 2005;Doughty et al, 2004) is proportional to the rate of responding previously emitted on the history-building contingency, rather than being a primary function of the rate of reinforcement in the history-building contingency (see Bouton, 1993Bouton, , 2002Nevin, 1979;Nevin et al, 1990). This effect was demonstrable in the results of Experiment 1 during the resurgence extinction test (previously higher rates showed greater resurgence), and also in the comparison of the Phase 1 and Phase 2 transitions in both experiments (previously higher rates showed greater resistance to contingency alteration).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously it has been demonstrated that the strength of history effects such as resistance to change (e.g., Lattal, 1989;Okouchi & Lattal, 2006;Reed & Doughty, 2005) and reinstatement (e.g., Doughty et al, 2005;Doughty et al, 2004) is proportional to the rate of responding previously emitted on the history-building contingency, rather than being a primary function of the rate of reinforcement in the history-building contingency (see Bouton, 1993Bouton, , 2002Nevin, 1979;Nevin et al, 1990). This effect was demonstrable in the results of Experiment 1 during the resurgence extinction test (previously higher rates showed greater resurgence), and also in the comparison of the Phase 1 and Phase 2 transitions in both experiments (previously higher rates showed greater resistance to contingency alteration).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that several history effects, such as resistance to change (Lattal, 1989;Okouchi & Lattal, 2006;Reed & Doughty, 2005), and reinstatement Doughty et al, 2004), appear in proportion to the rate at which the history response was emitted, rather than being a product of the history of rates of reinforcement. It is not currently known whether this also occurs in resurgence effects.…”
Section: Swansea University Swansea Walesmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, with reinforcement rate equated, it has been shown several times that lower response rates are more resistant than higher response rates (see also Blackman, 1968;Lattal, Reilly, & Kohn, 1998; but see Fath, Fields, Malott, & Grossett, 1983). Accounts offered for this greater resistance of lower response rates have included, among others, the aversiveness of high response rates (Lattal et al), response elasticity (Nevin et aI., 2001), and operant response class size (Doughty & Lattal, 2001;Reed & Doughty, 2005). Though the present results do not allow one to distinguish between these different accounts, they provide further evidence that the differential resistance that follows the training of unequal response rates can be predicted by the response-rate differences per se, rather than the contingencies supporting those rates.…”
Section: Discussionmentioning
confidence: 99%
“…Several experiments, however, have shown that manipulations of the response-reinforcer contingency do affect resistance to change when stimulus-reinforcer relations are equal across multiple-schedule components (Doughty & Lattal, 2001;Lattal, 1989;Nevin, Grace, Holland, & McLean, 2001;Reed & Doughty, 2005). Results from experiments in which equal rates of unsignaled delayed and immediate reinforcers are presented in different components of a multiple schedule provide clear examples inconsistent with the predictions of behavioral momentum theory (e.g., Bell, 1999;Grace, Schwendiman, & Nevin, 1998;Reilly & Lattal, 2004).…”
Section: ____________________________________________________________mentioning
confidence: 96%